Understanding Cross-Cultural Differences in Conceptualizing International Trade Patterns: A Neuroeconomic Perspective - Agbanyo, George Kwame; Wang, Yan (Frontiers in Neuroscience, 2022)
Neuroeconomics has been seldom used in investigating the impact of culture on international trade. This research proposes a scientific approach to investigate how cross-cultural differences contribute to the conceptualization of international trade patterns globally. International business relations are directly influenced by factors such as cultural variations which distinguish one foreign market from another. Therefore, the level of understanding these cultural differences is able to determine the success or not of business opportunities. In response to the scarcity of scientific investigation of cultural influence on international trade, the purpose of this study is to propose a neuroeconomic framework as a strategic instrument to elucidate the cross-cultural dimension of international commercial relations. Echoing this, our study uses cultural diversities and cognitive classifications established in literature to adopt a unique scientific tool for the conceptualization of international trade patterns across the world. This research establishes the cognitive mechanism of cross-cultural diversity, as a novel framework to conceptualize international trade patterns. By unveiling the cognitive process of cross-cultural diversity, this paper provides an instrument to unlock trade barriers of individualism and collectivism across nations.